1996
DOI: 10.1074/jbc.271.44.27388
|View full text |Cite
|
Sign up to set email alerts
|

Free Radical Generation as Induced by Ochratoxin A and Its Analogs in Bacteria (Bacillus brevis)

Abstract: Lipid peroxidation is considered as one of the manifestations of cellular damage in the toxicity of ochratoxin A (OA). OA; its three natural analogs, OB, OC, and O␣; and four synthetic analogs, d-OA, the ethylamide of OA (OE-OA), O-methylated OA (OM-OA), and the lactoneopened OA (OP-OA) were used to study free radical generation in bacteria with Bacillus brevis as a model system. The uptake of the different ochratoxins by B. brevis varied substantially depending on the molecular structures. Electron paramagnet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 31 publications
2
29
0
2
Order By: Relevance
“…Changes in renal enzyme activities were also observed in these cotreatment experiments [30,31]. The hypothesis of oxidative stress being involved in OTA-mediated genetic damage is further strengthened by evidence from studies revealing OTA-dependent lipid peroxidation and free radical formation in mammalian cells and other systems as well as in rats [32][33][34][35]. Decreased concentrations of vitamin E in plasma of rats [30], and of glutathione in liver of mice, in primary hepatocytes and in CV-1 cells have also been reported after OTA treatment [22,36,37].…”
mentioning
confidence: 66%
“…Changes in renal enzyme activities were also observed in these cotreatment experiments [30,31]. The hypothesis of oxidative stress being involved in OTA-mediated genetic damage is further strengthened by evidence from studies revealing OTA-dependent lipid peroxidation and free radical formation in mammalian cells and other systems as well as in rats [32][33][34][35]. Decreased concentrations of vitamin E in plasma of rats [30], and of glutathione in liver of mice, in primary hepatocytes and in CV-1 cells have also been reported after OTA treatment [22,36,37].…”
mentioning
confidence: 66%
“…In contrast, Hoehler et al 135 demonstrated vitamin E but not vitamin C to ameliorate the prooxidative effects of OTA in the chick model. The same group also demonstrated the generation of free radicals and malondialdehyde formation in Bacillus brevis 136 and in hepatocytes 137 following exposure to OTA and several of its analogs. Interestingly, the impact of OTB on free radical production in the B. brevis system was far less than that observed for OTA, which correlates with their relative in vivo and in vitro potencies.…”
Section: Is Ota Pro-apoptotic or Pro-cytotoxic?: A Role For Oxidativementioning
confidence: 94%
“…According to the authors, it is not yet clear whether the predominant toxic mechanism of OTA is of a genotoxic or epigenetic nature, such as induced cytotoxicity, oxidative cell stress or increased cell proliferation, due to an imbalance between proliferative and antiproliferative intracellular signal pathways. However, both the carcinogenicity and cytotoxicity of OTA have been related to free radical-mediated oxidative cell damage [42,43,44,45,46,47,48,49,50,51]. Schaaf et al .…”
Section: Ochratoxin Amentioning
confidence: 99%
“…Using a Bacillus brevis model, Hoehler’s et al . showed that OTA behaved as a cell pro-oxidant through mobilization of the Fe 2+ and Ca 2+ pathways, leading to uncoupling oxidative phosphorylation and increased production of hydroxyl radical via the Fenton reaction [45]. However, in other studies using OTA and structural analogs, a direct correlation between toxicity and iron chelating capacity was only partially supported [57].…”
Section: Ochratoxin Amentioning
confidence: 99%